Amygdala and hippocampus are symptomatogenic zones for central apneic seizures. (14th February 2017) - Lacuey, Nuria; Zonjy, Bilal; Londono, Luisa; Lhatoo, Samden D.
Abstract : Objective: To identify limbic sites of respiratory control in the human brain, and by extension, the symptomatogenic zone for central apnea. Methods: We used direct stimulation of anatomically, precisely placed stereotactic EEG electrodes to analyze breathing responses. We prospectively studied 3 patients who were explored with stereotactically implanted depth electrodes. The amygdala and hippocampus, as well as extralimbic sites (orbitofrontal, temporal tip, and temporal neocortex), were investigated. Results: Individual stimulation of the amygdala and hippocampal head consistently elicited central apnea in the expiratory phase, as did exquisitely focal hippocampal seizures. Conclusions: These findings confirm that hippocampus and amygdala are limbic breathing control sites in humans, as well as the symptomatogenic zone for central apneic seizures.